CITRA PEREMPUAN DALAM NASKAH DAF' AL-TURRAHĀT 'AN WĀJIBĀT AL-UMMAHĀT - Tiara, Andhika; Handayani, Rizqi; Ziah, Safurotun (Jurnal Lektur Keagamaan, 2025)
This article examines the construction of Muslim womanhood in Daf‘ al Turrahāt ‘an Wājibāt al Ummahāt (1939), a Hadhrami Indonesian manuscript authored by Habib Salim bin Jindan, to address the limited scholarly attention to early twentieth century religious manuscripts in gender studies. Existing research on Indonesian Muslim women has focused on reformist thinkers, fatwas, and modern interpretations, while the gender discourse embedded in Hadhrami textual traditions remains largely unexplored. This study fills that gap by producing a critical edition of the manuscript and analyzing its linguistic, thematic, and discursive features. The research employed qualitative philological methods, drawing on a single codex preserved at the Al Fachriyah Library. Data consist of the manuscript’s textual content, which is examined through textual criticism, transliteration, and contextual analysis to reconstruct the most reliable version of the text and interpret its gender concepts. The findings show, first, that the manuscript frames Muslim womanhood as a moral and ethical identity shaped by piety, religious knowledge, and social responsibility. Second, it articulates women’s roles through a biologically grounded framework that emphasizes motherhood, education of children, and moral cultivation. Third, the text reflects tensions between normative Islamic prescriptions and contemporary debates on women’s education and public participation. These findings demonstrate that the manuscript functions both as a religious treatise and as a cultural response to modernity. The study concludes that early Hadhrami Indonesian texts offer valuable insights for expanding gender discourse in Nusantara Islam.